(untitled) (Universal International Scientific Journal, 2026)
. This article analyzes the impact of globalization on the education system and the issues of ensuring mental health in the process of training competitive, highly qualified personnel. In the modern educational environment, increasing the level of psychological stability, stress resistance, and socio-psychological adaptation of students and specialists is considered an important factor. The study highlights innovative approaches to supporting mental health, including psychological training, digital psychological services, individual development programs, and pedagogical and psychological support mechanisms. It also substantiates ways to increase the effectiveness of training competitive personnel by creating a healthy psychological environment in the educational process in the context of globalization, ensuring the intellectual and emotional development of the individual.